2012
DOI: 10.1002/glia.22339
|View full text |Cite
|
Sign up to set email alerts
|

ICV‐transplanted human glial precursor cells are short‐lived yet exert immunomodulatory effects in mice with EAE

Abstract: Human glial precursor cells (hGPs) have potential for remyelinating lesions and are an attractive cell source for cell therapy of multiple sclerosis (MS). To investigate whether transplanted hGPs can affect the pathogenesis of experimental autoimmune encephalomyelitis (EAE), an animal model of MS, we evaluated the therapeutic effects of transplanted hGPs together with the in vivo fate of these cells using magnetic resonance imaging (MRI) and bioluminescence imaging (BLI). At 14 days post-EAE induction, mice (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Yet, despite the absence of transplanted human cells, we and other authors observed positive behavioral effects on a rat model of stroke [19–21]. A similar phenomenon has been observed in an experimental autoimmune encephalomyelitis (EAE) model by two separate groups of investigators [22, 23], where short-lived glial-restricted precursors were shown to have immunomodulatory abilities. Despite the lack of transplanted cell survival, positive effects from umbilical cord-blood-isolated stem cell transplantation were described in an ALS model [24], acute spinal cord injury [25], and brain hypoxia-ischemia [26].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Yet, despite the absence of transplanted human cells, we and other authors observed positive behavioral effects on a rat model of stroke [19–21]. A similar phenomenon has been observed in an experimental autoimmune encephalomyelitis (EAE) model by two separate groups of investigators [22, 23], where short-lived glial-restricted precursors were shown to have immunomodulatory abilities. Despite the lack of transplanted cell survival, positive effects from umbilical cord-blood-isolated stem cell transplantation were described in an ALS model [24], acute spinal cord injury [25], and brain hypoxia-ischemia [26].…”
Section: Introductionsupporting
confidence: 81%
“…There is some evidence showing that the presence of donor cells in the brain is not necessary for their positive effect to be exerted on the neurogenesis process. It has been shown that, even after the rapid elimination of transplanted cells [23], or after intravenous transplantation when no donor cells were observed in the host brain [19], the decrease in lesion size and the improvement in behavior were still observed. It seems that transplanted cells work indirectly in the host tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although one would expect cell survival to be essential for recovery, there is evidence that this is not the case. Indeed, for some applications, the rejection response or short-term immunomodulation of the local inflammatory environment may be sufficient to promote improvement [36]. Noninvasive monitoring of the survival or rejection of cells therefore provides a unique means to assess the presence of implanted cells in a given tissue.…”
Section: Assessing Survival and Differentiation Of Implanted Cellsmentioning
confidence: 99%
“…including MS, traumatic brain injury, stroke, amyotrophic lateral sclerosis and brain tumors, among others [10, [44][45][46][47][48][49]. In addition, the imaging of iron-labeled cancer cells in preclinical models of glioma and brain metastases has produced important information about cancer cell metastasis, invasion and dormancy [6,9].…”
Section: Review Hamilton Mallett and Fostermentioning
confidence: 99%
“…Immunomodulation has also been proposed as the mechanism of treatment for human glial precursor (hGP) cells [45]. Kim et al transplanted hGP cells directly into the lateral ventricle in a mouse model of EAE.…”
Section: • Stem Cell Trackingmentioning
confidence: 99%